Detection of Babesia bigemina in cattle of different genetic groups and in Rhipicephalus (Boophilus) microplus tick - Oliveira, M. C. S.; Oliveira-Sequeira, T. C. G. [UNESP]; Regitano, L. C. A.; Alencar, M. M.; Neo, T. A.; Silva, A. M.; Oliveira, Henrique Nunes de [UNESP] (Elsevier B.V., 2008)
Babesia bigemina infections were investigated in four genetic groups of beef cattle and in Rhipicephalus (Boophilus) microplus engorged female ticks. Blood samples and engorged female ticks were collected from 15 cows and 15 calves from each of the following genetic groups: Nelore, Angus x Nelore, Canchim x Nelore, and Simmental x Nelore. Microscopic examination of blood smears and tick hemolymph revealed that merozoites of B. bigemina (6/60) as well as kinetes of Babesia spp. (9/549) were only detected in samples (blood and ticks, respectively) originated from calves. PCR-based methods using primers for specific detection of B. bigemina revealed 100% infection in both calves and cows, regardless the genetic group. Tick infection was detected by nested-PCR amplifications showing that the frequency of B. bigemina was higher (P 0.01) in female ticks collected from calves (134/549) than in those collected from cows (52/553). The frequency of B. bigemina was similar in ticks collected from animals, either cows or calves, of the four genetic groups (P > 0.05). (C) 2008 Elsevier B.V. All rights reserved.
Keywords: beef cattle; tick; babesiosis; PCR